The Complete C++ Developer Course - Percival, Rob; Baugh, John (Packt Publishing, 2020)
Discover how to effectively use C++ for building real-world powerful applications About This Video Master the fundamentals of C++ programming Develop practical skills and terminology related to software development Learn how to apply the principles of object-oriented programming (OOP) like a pro In Detail Do you know that C++ is used by over 4 million developers worldwide? and in the US, a C++ developer earns around S100,000 a year. Learning C++ will add value to your CV and you will have skills that will give you a chance to work on amazing projects. Through this video course, you will learn C++ by building applications. The course starts by taking you through the learning objectives and helps you with the process of setting up the environment on Windows and macOS. Once you are ready to code, you will learn to build many interesting applications, such as Mad-Libs Clone, Jam of the Month, Parallel Array/Vectors, and Tic-Tac-Toe, to become familiar with C++ concepts such as variables, data types, operators, control statements, arrays, vectors, and functions. Moving along, you will again learn to build interesting projects to get to grips with classes, objects, exception handling, debugging, pointers, inheritance, and polymorphism. Finally, you will get an overview of templates, Standard Template Library (STL), pointers, and operator overloading. By the end of this course, you will have developed basic and advanced C++ skills needed to build modern and robust applications.
Online resource; Title from title screen (viewed November 30, 2020)
Keywords: Electronic videos